2014
DOI: 10.1002/2013ja019222
|View full text |Cite
|
Sign up to set email alerts
|

Detailed modeling and analysis of spacecraft plume/ionosphere interactions in low Earth orbit

Abstract: Detailed direct simulation Monte Carlo/particle-in-cell simulations involving the interaction of spacecraft thruster plumes with the rarefied ambient ionosphere are presented for steady thruster firings in low Earth orbit (LEO). A nominal mass flow rate is used to prescribe the rocket exit conditions of a neutral propellant species for use in the simulations. The charge exchange interactions of the steady plume with the rarefied ionosphere are modeled using a direct simulation Monte Carlo/particle-in-cell meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The flow conditions and physical models used to simulate the plume interaction with the ambient flow are described below. Details of the MPIC computational framework and physical models that are used in these simulations are outlined in Stephani and Boyd [2014].…”
Section: Direct Simulation Monte Carlo/particle-in-cell Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…The flow conditions and physical models used to simulate the plume interaction with the ambient flow are described below. Details of the MPIC computational framework and physical models that are used in these simulations are outlined in Stephani and Boyd [2014].…”
Section: Direct Simulation Monte Carlo/particle-in-cell Frameworkmentioning
confidence: 99%
“…MEX collisions for Pr − O, O − O and Pr − Pr are modeled using variable hard sphere [Bird, 1994] Table 4. Additional details regarding the collision models used in these simulations may be found in Stephani and Boyd [2014].…”
Section: Momentum Exchange/charge Exchange Collision Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Incorporating these effects is critical for capturing the development of the spacecraft plume in the plasma environment, particularly over large distances. Recent efforts [ Stephani and Boyd , ; Stephani et al , ] investigating spacecraft plumes in low Earth orbit (LEO) have demonstrated that interaction of the spacecraft neutral plume with the ambient plasma forms a relatively high‐density spacecraft ion plume. The propagation of this ion plume is determined primarily by the interaction with the magnetic field, but the development of the neutral spacecraft plume is also affected (albeit indirectly) by the magnetic field interaction owing to secondary charge‐exchange reactions.…”
Section: Introductionmentioning
confidence: 99%